+0  
 
0
139
3
avatar+2509 

#12 Help.

NotSoSmart  Feb 6, 2018
 #1
avatar+588 
+1

I believe that the inverse is f^-1(x) = -4 + x / 3

adore.nuk  Feb 6, 2018
 #2
avatar+12573 
+1

Repace 'y' with 'x'    and 'x' with 'y'  then sove for 'y'

x= 3y+12

x-12 = 3y

y = (x-12)/3    is the inverse

ElectricPavlov  Feb 6, 2018
 #3
avatar+87657 
+1

The above answers are identical...

 

-4 + x/3  =

 

-12/3 + x/3   =

 

[ x - 12 ]  / 3

 

 

 

cool cool cool

CPhill  Feb 6, 2018

12 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.